RESULTS OF CLINICAL TRIALS OF MEDICAL TREA TMENT OF RENAL CELL CARCINOMA IN 2014–2015 - A. M. Popov; O. B. Karyakin; A. D. Kaprin (Исследования и практика в медицине)
Over the last decade there have been significant changes in the approaches to the drug treatment of renal cell carcinoma. In clinical practice, there was a group of targeted drugs, the purpose of which has increased the life expectancy of patients with advanced kidney cancer. The studies devoted to the study of the sequence of destination targeted agents, combinations, studies of new drugs and to identify prognostic factors, are held.